G-CSF Intrauterine for Thin Endometrium, and Pregnancy Outcome - Ensieh Tehraninejad; Fateme Davari Tanha; Ebrahim Asadi; Koorosh Kamali; Elham Aziminikoo; Elahe Rezayof (Tehran University of Medical Sciences, 2015)
Objective:To evaluate effects ofG-CSF on a cancelled ART cycle due to thin endometrium. Materials and methods:In a nonrandomized clinical trial from January 2011 to January 2013 in two tertiary university based hospitals fifteen patients undergoing embryo transfer and with the history of cycle cancellation due to thin endometrium were studied. Intrauterine infusion of G-CSF was done on the day of oocyte pick-up or 5 days before embryo transfer. The primary outcome to be measured was an endometrium thickened to at least 6 mm and the secondary outcome was clinical pregnancy rate and consequently take-home baby. All previous cycles were considered as control for each patient. Results:The G-CSF was infused at the day of oocyte retrieval or 5 days before embryo transfer. The endometrial thickness reached from3.593±0.251 mm to 7.120±0.84 mm. The mean age, gravidity, parity, and FSH were 35.13± 9.531 years,3, 1 and32.78± 31.10 mIU/ml, respectively. The clinical pregnancy rate was 20%, and there was one missed abortion, a mother death at 34 weeks, and a preterm labor at 30 weeks due to PROM. Conclusion:G-CSF may increase endometrial thickness in the small group of patients who had no choice except cycle cancellation or surrogacy.